PROFITABILITY AND TIME CONSUMPTION AS INFLUENCED BY VARIOUS WEED CONTROL METHODS IN CURCUMA AMADA ROXB. - Samuel Oluwaseun Osunleti; S T O Lagoke; P M Olorunmaiye; O R Adeyemi; Elizabeth O Olatunde; Ayodeyi O Ajani; O Olaogun (Agricultural Socio-Economics Journal, 2022)
To determine the profitability and time consumption of various weed control options in mango ginger, the field trials were conducted at the Teaching and Research Farm, Federal University of Agriculture Abeokuta (07° 20 N, 3° 23 E, 159 m above sea level) in the forest – savannah transition agroecology of Nigeria in the early cropping seasons of 2016 and 2017. Randomized complete block design (RCBD) was used to evaluate ten weed control strategies and replicated three times. Data collected on weed cover, plant biomass, and rhizome yield were analyzed using ANOVA, and treatment means were separated using the least significant difference at p0.05. Results indicated that the highest man days in weeding was observed on the plots weeded five times at 4, 8, 12, 16 and 20 weeks after planting (WAP), while application of pre emergence herbicides generally reduced time spend on weeding. Despite the fact that weeding at 4, 8, 12, 16, and 20 WAP had the maximum rhizome production and yielded the highest gross return, application of oxyfluorfen (oxyf) at 0.24 kg a.i/ha as a pre and post emergence herbicide yielded the highest benefit cost ratio.